1999
DOI: 10.3109/09513599909167565
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nicotine, cotinine, anabasine and cigarette smoke extract on human granulosa cell progesterone and estradiol synthesis

Abstract: To reveal the well known effect of smoking on the incidence of early abortion, the possible effects of cigarette alkaloids on progesterone and estradiol synthesis were investigated. A suspected cause for early spontaneous abortion is corpus luteum insufficiency. The present experiments evaluate the effects of cigarette smoke alkaloids on progesterone and estradiol biosynthesis. Human granulosa cells were obtained from patients undergoing in vitro fertilization and embryo transfer treatment because of infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
0
22
0
4
Order By: Relevance
“…Exposure of cultured human granulosa cells to smoke or nicotine has given mixed results with respect to estradiol synthesis. In some studies (Barbieri et al, 1986b;Vidal et al, 2006), inhibition of estradiol synthesis was reported following treatment with mainstream smoke, environmental tobacco smoke, or nicotine, but similar inhibition was not found by others (Bodis et al, 1997;Gocze et al, 1999;Weiss and Eckert, 1989). In a recent study, human luteinized granulosa cells were exposed to medium conditioned by environmental tobacco smoke and showed a decrease in both estrogen and progesterone production (Vidal et al, 2006).…”
Section: Ovarian Follicular Explantsmentioning
confidence: 85%
“…Exposure of cultured human granulosa cells to smoke or nicotine has given mixed results with respect to estradiol synthesis. In some studies (Barbieri et al, 1986b;Vidal et al, 2006), inhibition of estradiol synthesis was reported following treatment with mainstream smoke, environmental tobacco smoke, or nicotine, but similar inhibition was not found by others (Bodis et al, 1997;Gocze et al, 1999;Weiss and Eckert, 1989). In a recent study, human luteinized granulosa cells were exposed to medium conditioned by environmental tobacco smoke and showed a decrease in both estrogen and progesterone production (Vidal et al, 2006).…”
Section: Ovarian Follicular Explantsmentioning
confidence: 85%
“…30 The hypothesis that smoking may inhibit progesterone synthesis has been evaluated in animal and human cells out- side the brain with inconsistent results. 31,32 However, given these observations, interactive effects could be explored and may explain some of the inconsistencies in human studies. 11,29,[33][34][35][36][37][38][39][40][41] It should be noted that smoking was crudely recorded in this study; data on number of cigarettes smoked, type of cigarette and duration of use was not included on the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, morphine inhibits the hydroxylation of progesterone in vivo (Rane and Ask 1992) and stimulates the activity of 3α-hydroxysteroid dehydrogenase in the brain in vitro (Jaworska-Feil et al 2000). Moreover, cigarette alkaloids inhibit both progesterone synthesis in cultured human granulosa cells (Gocze et al 1999) and specific P450 enzymes in rat adrenal and testicular cells (Kasson and Hsueh 1985;Barbieri et al 1987). Repetitive exposure to nicotine or morphine induces adaptive changes in the central nervous system that lead to the development of tolerance and physical dependence.…”
Section: Discussionmentioning
confidence: 99%